Analysis of Service Quality Performance in Higher Education Uses Importance Performance Competitor Analysis (IPCA) - Mochamad Santoso; Andriani Kusumawati; I Gede Eko Putra Sri Sentanu (Sekolah Pascasarjana Universitas Brawijaya, 2020)
This study aims to determine the performance of service quality from students' perceptions of study programs in tertiary institutions using Gap analysis with measurement instruments using Higher Education Performance (HedPerf) modified into 5 (five) factor/dimension structures. The method used in this study is a quantitative method with a descriptive approach, sampling using the Probability Sampling technique in Proportioned Stratified Random Sampling. Data analysis uses the Importance Performance Competitor Analysis (IPCA) method which is a form of analysis that answers criticism of the IPA analysis, especially regarding competitor factors. Where data samples are taken from study programs which are the focus of research and from study programs that become competitors. The results obtained from this study indicate that 10 service items require immediate action to improve the quality of service performance. Especially from the variable reputation that has a dominant position to be immediately reformed.